A National Laboratory Perspective: The Impact of the Covid-19 Pandemic on the Management of Patients With Non-Communicable Disease in South Africa: Impact of COVID-19 on patients with noncommunicable diseases - Kruger, Elsie C.; Van der Westhuizen, Diederick J.; Erasmus, Rajiv T.; Banderker, Razia B.; Jacob, Doreen; Moodley, Nareshni; Ngxamngxa, Unathi; Kengne, Andre P.; Zemlin, Annalise E. (Disaster medicine and public health preparedness, 2024)
The aim of this study was to determine the impact of the COVID-19 pandemic on test requests for the diagnosis and routine care of patients with various non-communicable diseases (NCD) across South Africa (SA). A retrospective audit of laboratory test requests received from hospital outpatient departments and primary healthcare facilities across SA was performed. The following analytes were studied: glycated hemoglobin (HbA1c), lipids profiles, thyroid-stimulating hormone (TSH), and thyroxine (fT4), as well as triiodothyronine (fT3), serum protein electrophoresis (SPE), serum free light chains (SFLC), and prostate specific antigen (PSA); these tests were used as a proxy of NCD detection and follow-up. Requests received during the 3 waves of the pandemic were compared to requests received within the same period during 2017 - 2019. During the first wave, requests for all analytes were reduced, with the biggest reduction observed for SPE (- 37%); TSH (- 29%); fT4 (- 28%); and HbA1c (- 25%). Requests received from urban facilities showed a larger decrease compared to those from rural facilities. During the third wave there was an increase in requests for all analytes; the biggest increase observed was for fT3 (21%) and HbA1c (18%). The COVID-19 pandemic had a significant impact on the South African population receiving care in the public healthcare sector.